ANALYSIS AND DESIGN OF KNOWLEDGE INTEGRATION TEST INSTRUMENTS (SCIENCE-ISLAM) ON THE SUBJECT OF THE CREATION OF THE UNIVERSE AND SOLAR SYSTEM - Ardiansyah; Mohammad Jamhari, Ratman (Adisam Publisher, 2024)
The Islamic conception of knowledge does not limit knowledge about reality to that obtained through experimentation and theoretical reasoning only. Natural knowledge that is understood does not just answer human desires if we can accommodate revelation and intuition, including the spiritual and physical aspects of humans and the cosmos. Understanding the integration of Islamic values in natural science (science) learning is implied in the Qur'an. The Koran does not conflict between science and religion. In fact, in many of His verses it is emphasized that humans should always think about events in nature to strengthen their religious beliefs. Science in this case is also not a separate part of religion. Science is an integral part of the Islamic religion. The Koran states that science, like the science of human life, is an integral part of religion. Science teaches humans how to manage nature, carry out various processes, and produce things for life's needs. Meanwhile, religion teaches humans about value systems. Religion teaches the value of piety towards the Khaliq and the value of kindness towards others.